Evaluation of Foramen Magnum for Sex Determination among the Population of Dakshina Kannada District: A Retrospective CBCT Study - Junaid Ahmed; null Namrata; Nanditha Sujir; Nandita Shenoy; Archana M.; Srikant Natarajan (The Scientific World Journal)
Background. This study aims to evaluate the accuracy rate of foramen magnum dimensions in determining sex among the South Indian population using discriminant functional analysis. Methods. An observational study in which CBCT images from 200 full field of view (FOV) scans were analysed. The dimensions of the foramen magnum were measured. Intra- and interobserver reliability were calculated. Independent t-tests were used to compare the various parameters between sexes. Stepwise discriminant function analysis was used to determine sex. Results. A total of 200 CBCT scans were included in the study. The mean age (±SD) was 25.66 (±7.11) years among males and 24.64 (±5.12) years among females. The measurements and the circumference of the foramen magnum were significantly (p<0.001) greater in males than in females. The univariate analysis of foramen magnum measurements reached an accuracy rate of 73.5% in sex determination. The discriminant function analysis combining the foramen magnum measurements and circumference yielded an overall predictability rate of 66.5% for determining sex. Conclusion. Taking into account the predictability rate of sex based on foramen measurement in the present population, it can be concluded that its applicability should be limited to cases associated with fragmentary skull bases.